Book Reviews (The ecumenical review, 1954)
Book reviewed in this article: CHRIST IN THE TWENTIETH CENTURY: The Christ of the New Testament, by A. W. Argyle. CHRIST IN THE TWENTIETH CENTURY: The Patristic Doctrine of Redemption, by H. E. W. Turner. CHRIST IN THE TWENTIETH CENTURY: The Cosmic Christ, by Allan D. Galloway. CHRIST IN THE TWENTIETH CENTURY: The Problem of Christ in the Twentieth Century. An Essay on the Incarnation, by W. R. Matthews. CHRIST IN THE TWENTIETH CENTURY: Jesus Christ and his Cross. Studies on the saving work of Christ, by F. W. Dillistone. HISTORY OF THE CHRISTIAN HOPE: Die Verkuendigung des Reiches Gottes in der Kirche Jesu Chrisi. Zeugnisse aus allen Jahrhunderten und allen Konfessionen, by Ernst Staehelin. HISTORY OF THE CHRISTIAN HOPE: His Appearing and his Kingdom: The Christian Hope in the Light of its History, by T. Francis Glasson. SPEAKING THE CATHOLIC TRUTH IN LOVE: Les voies de l'unité chrétienne, Doctrine et spiritualité, by C. J. Dumont. WHO IS MY NEIGHBOUR?: Colour, Unsolved Problem of the West, by Ben J. M. Marais. WHO IS MY NEIGHBOUR?: The Catholic Church and the Race Question, by the R. P. Yves M.-J. Congar O. P. UNESCO, Paris, 1953. WHO IS MY NEIGHBOUR?: The Ecumenical Movement and the Racial Problem, by W. A. Visser 't Hooft. ECUMENICAL PROFILES: Oekumenische Profile, Gestalten der Einen Kirche in aller Welt, im Auftrag des Oekumenischen Ausschusses in Berlin herausgegeben von Günter Gloede.